2019
DOI: 10.2147/ppa.s235711
|View full text |Cite
|
Sign up to set email alerts
|

<p>Interactive Network Platform Improves Compliance and Efficacy of Subcutaneous Immunotherapy for Patients with Allergic Rhinitis</p>

Abstract: Background: Allergic rhinitis (AR) is a common chronic inflammatory disease of nasal mucosa worldwide, and its symptoms seriously affect the lives of patients. Subcutaneous immunotherapy (SCIT) is an effective treatment for AR, but it is also associated with low patient compliance and difficulties in fully achieving therapeutic effects. Objective: In this prospective randomized controlled study, we verified the effects of an interactive network platform named "U breath" in improving patient compliance and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Epidemiological studies showed that AR affected at least half a billion people worldwide, and more than half of them were moderate to severe [ 3 ]. In China, the prevalence of AR even rises to 34.3% of the general population, and rates still continue to increase [ 4 , 5 ]. Although not life threatening, AR exhibits a negative influence on people's quality of life and their work production and brings about a high medical cost on individuals and society.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies showed that AR affected at least half a billion people worldwide, and more than half of them were moderate to severe [ 3 ]. In China, the prevalence of AR even rises to 34.3% of the general population, and rates still continue to increase [ 4 , 5 ]. Although not life threatening, AR exhibits a negative influence on people's quality of life and their work production and brings about a high medical cost on individuals and society.…”
Section: Introductionmentioning
confidence: 99%
“…A mean posttreatment difference of –1.5 (95% CI, –2.4 to –0.5; P = .002) was demonstrated for the EpSS and –1.7 (95% CI, –2.1 to –1.2; P < .00001) for the PSQI. Twenty-two studies 26-47 informed on the sleep domain of the RQLQ, while 14 studies 26,29-31,33,35-38,41-43,45,48 reported the total RQLQ after treatment. A mean posttreatment difference of –1.1 (95% CI, –1.2 to –0.9; P < .00001) was calculated for the RQLQ sleep domain and –1.4 (95% CI, –1.6 to –1.1; P < .00001) for RQLQ total.…”
Section: Resultsmentioning
confidence: 99%
“…00001) for the PSQI. Twenty‐two studies 26–47 informed on the sleep domain of the RQLQ, while 14 studies 26,29–31,33,35–38,41–43,45,48 reported the total RQLQ after treatment. A mean posttreatment difference of –1.1 (95% CI, –1.2 to –0.9; P <.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, a study showed that self-media management can markedly improve the compliance of SLIT patients ( 18 ). At the same time, some studies illustrated that Internet-based interactive and mobile platforms can improve compliance with subcutaneous immunotherapy ( 19 , 20 ). Therefore, our team decided to use the mobile medical APP and WeChat to follow-up SLIT patients; compared with patients who received telephone follow-up in the past, we found that Internet follow-up can significantly improve the compliance of SLIT patients.…”
Section: Discussionmentioning
confidence: 99%